Corporate Social Responsibility (CSR) Communication Strategy in an Effort to Form Corporate Image at PT. Resilient Superpower - Shavina, Siti Noer; Andryani, Kristina; Febrianty, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2025)
To maintain a good corporate image, it is necessary to have strategies and approaches that align with the company's needs and primary goals. On the other hand, effective communication strategies between the company, stakeholders, and the public are also essential in the implementation process of programs to shape the corporate image. One way to achieve this is by implementing Corporate Social Responsibility (CSR) using communication strategies. The communication strategy in a company's Corporate Social Responsibility (CSR) essentially involves planning and management aimed at achieving specific targets in the communication process. Thus, the CSR/PPM programs planned by the company can run smoothly. Therefore, this research is titled